Sistem Pakar untuk Mendiagnosa Penyakit Persendian Menggunakan Metode Certainty Factor - Leidiyana, Henny; Hariyanto, Risvan Dwi (Jurnal Komtika (Komputasi dan Informatika), 2020)
If someone feels unwell, they will usually make a diagnosis and find the solutions before deciding to consult a doctor. As with joint disease with symptoms of pain that are still mild, there is no time to go to the doctor, fees, or other reasons. Especially now through information via the internet can be easily obtained. To assist in identifying and improving the accuracy of diagnosis, it is necessary to have a web-based expert system application to diagnose joint disease using certainty factor methods. The research method used is using SDLC (Software Development Life Cycle). An expert system that has been made can be used as early detection and get solutions for joint diseases and preventive measures to treatment